Interesting Features of a Career of Supply Chain Manager - St. Dwiarso Utomo; Zaky Machmuddah; Khaeronisa Khaeronisa; Suhana Suhana (International Journal of Supply Chain Management, 2020)
Abstract— Supply Chain Management Career Information and Education Requirements is the main objective of the current research. So for this purpose empirically whether the supply chain manager profession is still in demand by students in the industrial revolution 4.0 era is considered. Factors that influence students' career interests to be Supply Chain Managers are examined in th study. Accounting study program students in Semarang City Indonesia are used as the population in research. The sample was obtained as many as 312 respondents using a random method. SEM with Warp PLS is used as a data processing technique. The test results prove that 58.5% of respondents chose a career as an Supply Chain Manager, 38.2% chose to become civil servants, 3.3% chose to become entrepreneurs, this proves that the career of becoming an Supply Chain Manager is still in demand by accounting students. Financial rewards, labor market considerations, work environments, professional recognition, and social value have significant effects on career interests as supply chain managers. Gender moderates the influence of social values on career interests as Supply Chain Managers. However, professional training has no effect on career interests as supply chain managers. It means that the research succeeded in proving that there are several factors influencing the interests of career accounting students as Supply Chain Managers in the era of the industrial revolution 4.0.